Bovine humoral immune responses to Haemonchus placei excretory secretory antigens - Schallig, Henk D. F. H.; Moyo, Doreen Z.; Hendrikx, Wim M. L.; Eysker, Maarten (Elsevier, 2015)
immune response of calves against excretory secretory (ES) products of adult Haemonchus placei was studied. The ES products of adult H. placei comprise at least ten polypeptides with molecular weights ranging from 10 to over 100 kDa. A primary infection of calves with H. placei did not result in a marked elevation of IgG serum antibodies reactive to ES antigens as demonstrated by ELISA. Immunoblotting experiments revealed that sera of primary infected calves recognised a 50 kDa antigen in most cases. An increase in the level of serum IgG antibodies was observed after trickle infections. The secondary immune response coincided with the recognition of a group of three ES antigens of around 50-55 kDa and one protein with a molecular weight of 24 kDa.